515 Late-Breaking: Effects of Dietary Phytase with or without Multi-carbohydrase Supplementation on Growth Performance, Nutrient Digestibility, and Bone Traits in Nursery Pigs. (8th October 2021) - Adeshakin, Olumide E; Koo, Bonjin; Patterson, Robert; Nyachoti, Martin
Abstract: The aim was to determine the effects of supplementing increasing doses of phytase (PHY) alone or in combination with multi-carbohydrase (MC) blend to a P-deficient diet for nursery pigs on growth performance, nutrient digestibility, and metacarpal bone characteristics. A total of 192 weaned pigs (7.7 ± 0.05 kg BW) were allotted to 1 of 8 dietary treatments each with 8 replicates in a randomised complete block design based on initial body weight. Diets consisted of a P-deficient negative control (NC), NC + 250 FTU/kg (TRT1), NC + 500 FTU/kg (TRT2), NC + 1, 000 FTU/kg (TRT3), NC + 0.2g/kg MC (TRT4), TRT4 + 250 FTU/kg (TRT5), TRT4 + 500 FTU/kg (TRT6), and TRT4 + 1, 000 FTU/kg (TRT7). Fecal samples (d 18, 19, and 20) and metacarpal bones (d21) were collected to determine apparent total tract digestibility (ATTD) of energy and nutrients and bone mineralization, respectively. Data were analyzed using the MIXED procedure of SAS with orthogonal polynomial contrast statements with a pen as an experimental unit for growth performance and digestibility and 1 pig per pen for bone traits. During week 2, MC supplementation tended to increase (P = 0.05) body weight whereas by week 3, increasing doses of PHY linearly (P < 0.05) increased average daily gain (ADG). Overall, PHY supplementation had a quadratic effect (P < 0.05) increasing ADG. However, there was an interaction (P < 0.05) whereby PHY and MC in combination acted synergistically to increase percentage of ash and P ATTD. Phytase had linear (P < 0.05) and quadratic (P < 0.05) by increasing fat-free dry weight, ash content, and P in metacarpal bone. In conclusion, increasing levels of PHY quadratically improved growth performance, nutrient digestibility, and bone traits of pigs fed a P-deficient diet.